2019
DOI: 10.32861/ajc.410.90.95
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Typha Australis Stems in Bioethanol Production Using Enzymatic Hydrolysis and Biofermentation

Abstract: The present study aims to valorize the Typha australis stems, through second-generation bioethanol production using enzymatic hydrolysis and fermentation. The monitoring of fermentation kinetics parameters, such as pH, density, length of fermentation, and the Brix, indicated a great variability of these parameters during the fermentation process of the must with three Saccharomyces cerevisiae strains, such as Angel brand Thermal-tolerant alcohol active dry yeast, Angel brand super alcohol active dry yeast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The nutrient supply therefore has a significant influence on the fermentation kinetics, especially at the level of S3. These results were more in line with the indications in the literature on the nutritional requirements of the yeast Saccharomyces cerevisiae [30] . At the level of all the physicochemical parameters followed, in the presence of the growth factor, a much more rapid evolution was observed.…”
Section: Fig 4: Limit Attenuation Of Non-enriched Mustssupporting
confidence: 91%
See 1 more Smart Citation
“…The nutrient supply therefore has a significant influence on the fermentation kinetics, especially at the level of S3. These results were more in line with the indications in the literature on the nutritional requirements of the yeast Saccharomyces cerevisiae [30] . At the level of all the physicochemical parameters followed, in the presence of the growth factor, a much more rapid evolution was observed.…”
Section: Fig 4: Limit Attenuation Of Non-enriched Mustssupporting
confidence: 91%
“…The presence of nutrients for yeasts in a culture medium has a proven positive influence on ethanol production [13] . Some researchers have also shown that the presence in a fermentation broth of extracts of yeast, urea, ammonium ions [30] , calcium and magnesium [31] , has effects protectors on both cell growth and viability. It also promotes an acceleration of fermentation speed and ethanol production [32] .…”
Section: Effect Of Urea On Ethanol Contentmentioning
confidence: 99%
“…In Benin, the proliferation of this plant is a real problem for the rivers in the valley. This plant has been valorized into bioethanol produced by enzymatic hydrolysis and bio-fermentation, which can be used as a biofuel substitute for gasoline, reducing CO 2 by 90% [22]. A limited number of researchers have studied the hydric, thermal and mechanical characterization of Typha australis using clay or cement as a binder.…”
Section: Introductionmentioning
confidence: 99%